Documenting Presence - Habib, Jasmin (Anthropologica, 2018)
This article presents us with a number of letters written by Eeyou that assert their autonomy and their relationships to Eeyou Istchee. The first set of letters were written in the 1930s and reveal not only the sovereign status of the Eeyou and their collective engagements with colonial agents, but the symbiosis that existed between the Hudson’s Bay Company and Indian Affairs Canada. In the second set of letters, written in the 1970s by community members John and Maryann Sam and Walter Pachanos, one gains intimate as well as experiential knowledge of the land, and appeals for its joint protection in the face of threats posed by Hydro-Quebec’s development plans. These letters not only document Eeyou presence and sovereignty, they alert to the long history of entanglements and of Eeyou-initiated proper relationships with colonial agents in what can be described as a poetics of engagement and resistance.